Fear of COVID-19 in residents of a Human Settlement in Puente Piedra, Lima - Castillo-Zelaya, Betsabe Kelita (2021)
Objectives: Identify the fear of COVID-19 in residents of a Human Settlement in Puente Piedra, Lima. Materials and methods: This research was developed from a quantitative approach, its design was descriptive-transversal. The population consisted of 500 participants. The data collection technique was the survey and the measurement instrument was the COVID-19 Fear Scale (FCV-19S), which consists of 7 items and 2 dimensions. Results: Regarding the participants, men represent 45.4% (n = 227) and women 54.6% (n = 273). In relation to fear of COVID-19, the high level prevailed with 58% (n = 209), followed by the middle of the medium level in 21.8% (n = 109) and low with 20.2% (n = 101). Regarding the dimensions, in reactions to emotional fear, a medium level prevailed with 50.2% (n = 252), followed by high in 35.4% (n = 177) and low with 14.2% (n = 71); in somatic expressions of fear, the low level prevailed with 48.4% (n = 242), followed by the medium in 42% (n = 210) and high with 9.6% (n = 48). Conclusions: Regarding the fear of COVID-19, the medium level predominated, followed by high and low. In relation to its dimensions, in reactions to emotional fear the medium level predominated, followed by the high and low level; in somatic expressions of fear, the low level predominated, followed by the medium and high. Regarding sex, women are more afraid of COVID-19 than male participants.